Afghanistan : Between Hope and Fear - Bronstein, Paula; Foreword by Barker, Kim; Introduction by Lamb, Christina (Austin University of Texas Press, 2016)
State or Province Government Publication.
Include Color Illustrations.
Between Hope and Fear.
Keywords: Photojournalism -- Women -- Women and war